Closing the loop by expanding the scope: using learning analytics within a pragmatic adaptive engagement with complex learning environments - Johnson, Lesley; Devis, Deborah; Bacholer, Cameron; Leonard, Simon N. (Frontiers in Education, 2024)
Closing the loop' in Learning Analytics (LA) requires an ongoing design and research effort to ensure that the technological innovation emerging from LA addresses the actual, pragmatic problems of educators in everyday learning environments. An approach to doing so explored this paper is to design LA as a part of the human systems of activity within an educational environment, as opposed conceptualising LA as a stand-alone system offering judgement. In short, this paper offers a casestudy of how LA can generate data representations that can provide the basis for expansive and deliberative decision-making within the learning community. The case-study provided makes use of Social Network Analysis (SNA) to monitor the changing patterns of decision making around teaching and learning in a very large Australian college over several years as that college embarked on an organised program of practitioner research. Examples of how the various SNA metrics can be translated into matters of pragmatic concern to the college, its leaders, teachers and students, are provided and discussed.